BRANDING: MENINGKATKAN BRAND AWARENESS WISATA PANTAI LON MALANG SOKOBANAH KABUPATEN SAMPANG - Fazlurrahman Adenan Ramdani Saleh; Aileena Solicitor Costa Rica El Chidtian; Aphief Tri Artanto (Universitas Negeri Makassar, 2022)
Beach tourism is very popular with many local and foreign tourists. The beach is a prima donna for foreign tourists who come to visit the State of Indonesia, the beach can also be a tool to develop the potential and economy of the community around the coast. The main factor supporting the development of potential and the economy is marked by the number of tourists who come to visit. In designing a brand on Lon Malang beach tourism, Sokobanah which is informative and creative in the form of Brand Awareness of Lon Malang Beach Tourism. Brand awareness itself aims to provide creative and informative information, and can indirectly improve a good image for Sampang Regency. This design uses a qualitative method with 2 stages, namely in-depth interviews and field observations. The approach taken using these 2 stages can produce a design concept with the keyword